Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-68383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Speed Ratio and Axial Spacing Variations on the Performance of a High Aspect Ratio, Low Speed Contra-Rotating Fan

Abstract: This paper explores the effect of speed ratio and axial spacing between high aspect ratio, low speed contra-rotating pair rotors on their aerodynamic performance. The blades were designed with a low hub-tip ratio of 0.35 and an aspect ratio of 3.0. Numerical and experimental studies are carried out on these contra-rotating rotors operating at a Reynolds number of 1.258 × 105 (based on blade chord). The first and second rotors were designed to develop a pressure rise of 1100 Pa and 900 Pa, respectively, for tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…10,11 To obtain a deeper insight into the flow physics in CRAC, a large amount of work has been carried out on the effects of some major factors such as rotor stagger angle, pitch-chord ratio, inlet distortion, casing treatment, speed ratio of the two rotors, axial spacing between two rotors, etc. [12][13][14][15][16][17][18][19] Results showed that those factors have significant impacts on the performance of CRAC. So as to understand the tip clearance size effect on the overall performance and TLF, Gao et al 20 and Wang et al 21 have conducted steady numerical simulations on several tip clearance sizes for both rotors.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 To obtain a deeper insight into the flow physics in CRAC, a large amount of work has been carried out on the effects of some major factors such as rotor stagger angle, pitch-chord ratio, inlet distortion, casing treatment, speed ratio of the two rotors, axial spacing between two rotors, etc. [12][13][14][15][16][17][18][19] Results showed that those factors have significant impacts on the performance of CRAC. So as to understand the tip clearance size effect on the overall performance and TLF, Gao et al 20 and Wang et al 21 have conducted steady numerical simulations on several tip clearance sizes for both rotors.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the inverse design concept with stacking of the front rotor along trailing edge and along leading edge for the rear rotor. Mistry and Pradeep 14,15 have recently reported design and preliminary performance analysis of a high aspect ratio contra-rotating axial flow fan stage.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies showed that variable speed matching can improve the work stability [16]. Mistry and Pradeep [17,18], through experiments and numerical simulations, reported a study of speed ratio on the performance of a contrarotating fan stage. Results showed that with increasing the speed ratio, the strong suction generated by the second rotor improves the stage pressure rise.…”
Section: Introductionmentioning
confidence: 99%